Enhancing Solar Thermal Energy Storage via Torsionally Modified TPMS Structures Embedded in Sodium Acetate Trihydrate - Martin Beer; Radim Rybár (Energies)
This study focuses on the numerical analysis of the impact of geometric modifications of sheet-gyroid structures on heat transfer in thermal energy storage systems utilizing sodium acetate trihydrate as a phase change material. The aim was to enhance the thermal conductivity of SAT, which is inherently low in the solid phase, by embedding a thermally conductive metallic structure made of aluminum alloy 6061. The simulations compared four gyroid configurations with different degrees of torsional deformation (0°, 90°, 180°, and 360°) alongside a reference model without any structure. Using numerical analysis, the study evaluated the time required to heat the entire volume of SAT above its phase transition temperature (58 °C) as well as the spatial distribution of the temperature field. The results demonstrate that all gyroid configurations significantly reduced the charging time compared with the reference case, with the highest efficiency achieved by the 360° twisted structure. Temperature maps revealed a more uniform thermal distribution within the phase change material and a higher heat flux into the volume. These findings highlight the strong potential of TPMS-based structures for improving the performance of latent heat thermal energy storage systems.